Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Manufaktur Di Bursa Efek Indonesia - Davin Azaria Purnama, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This study is to determine the effect of leverage, company size, return on assets, and earnings per share on the value of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The sample was selected by purposive sampling method and the valid data were 75 companies. The data processing technique uses multiple regression analysis assisted by the E-views 11 program. The results of this study indicate that all independent variables simultaneously affect firm value. The t test results show that leverage has a positive effect on firm value, firm size has a negative effect on firm value, return on assets and earnings per share have no effect on firm value. The research implication is the need to improve manager's performance to create company success so that the company's value will increase.